Polymicrogyria is Associated With Pathogenic Variants in PTEN. Issue 6 (8th October 2020) - Shao, Diane D.; Achkar, Christelle M.; Lai, Abbe; Srivastava, Siddharth; Doan, Ryan N.; Rodan, Lance H.; Chen, Allen Y.; ,; Poduri, Annapurna; Yang, Edward; Walsh, Christopher A.
Abstract : Objective: Congenital structural brain malformations have been described in patients with pathogenic phosphatase and tensin homologue ( PTEN ) variants, but the frequency of cortical malformations in patients with PTEN variants and their impact on clinical phenotype are not well understood. Our goal was to systematically characterize brain malformations in patients with PTEN variants and assess the relevance of their brain malformations to clinical presentation. Methods: We systematically searched a local radiology database for patients with PTEN variants who had available brain magnetic resonance imaging (MRI). The MRI scans were reviewed systematically for cortical abnormalities. We reviewed electroencephalogram (EEG) data and evaluated the electronic medical record for evidence of epilepsy and developmental delay. Results: In total, we identified 22 patients with PTEN pathogenic variants for which brain MRIs were available (age range 0.4–17 years). Twelve among these 22 patients (54%) had polymicrogyria (PMG). Variants associated with PMG or atypical gyration encoded regions of the phosphatase or C2 domains of PTEN. Interestingly, epilepsy was present in only 2 of the 12 patients with PMG. We found a trend toward higher rates of global developmental delay (GDD), intellectual disability (ID), and motor delay in individuals with cortical abnormalities, although cohort size limited statistical significance. Interpretation: Malformations of cortical development, PMG in particular, represent an under‐recognized phenotype associated with PTEN pathogenic variants and may have an association with cognitive and motor delays. Epilepsy was infrequent compared to the previously reported high risk of epilepsy in patients with PMG. ANN NEUROL 2020;88:1153–1164